Key Opinion Consumers (KOCs) and Consumer Behavior on Xiaohongshu: An Empirical Study via the Authenticity - Interactivity-Professionalism (AIP) Framework - Yan, Zhenwei; Rehman, Asad Ur (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
This study investigates the influence of Key Opinion Consumers (KOCs) on consumer behavior within Xiaohongshu, a leading social commerce platform in China, by proposing an integrated Authenticity-Interactivity-Professionalism (AIP) framework. Drawing on the Elaboration Likelihood Model (ELM) and Social Identity Theory, the framework aims to unpack how KOCs shape consumer trust and purchase intention through three core dimensions. A mixed-methods approach was employed, combining quantitative analysis of 500 user surveys, qualitative coding of 100 high-engagement KOC posts, and in-depth interviews with 20 KOCs across beauty, parenting, and travel niches. Results indicate that authenticity (β=0.47, p<0.001) and interactivity (β=0.34, p<0.01) are significant antecedents of consumer trust, while professionalism (β=0.41, p<0.001) directly drives purchase intention. Notably, KOCs’ unfiltered content and real-time interactions outperform traditional Key Opinion Leaders (KOLs) in triggering impulse purchases, as raw authenticity mitigates skepticism and live engagement enhances immediacy. This study contributes to user-generated content (UGC) marketing theory by validating the AIP framework and offers actionable insights for brands and platforms to leverage KOCs’ grassroots influence.